(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the significance of active and healthy ageing for elderly internally displaced persons (IDPs) who face dual challenges – age-related changes and the consequences of forced displacement. It emphasizes the role of health-recreational physical activity (HRPA) in maintaining this vulnerable population’s physical, mental, and social well-being. HRPA improves overall physical condition, reduces the risk of chronic diseases, enhances cognitive functions, and increases social interaction and adaptation to new living conditions. The article analyzes modern active and healthy ageing concepts defined by WHO, the European Commission, and domestic scientists. Key aspects of supporting the quality of life of IDPs through access to medical and rehabilitation services, social integration, favorable living conditions, and participation in state and local initiatives are considered. Regular physical activity has numerous benefits for the elderly, including improved physical health, increased mobility, reduced risk of chronic diseases, and improved psychological state. For elderly IDPs, these benefits are particularly significant as they help overcome the stress associated with displacement and promote social integration into new communities. HRPA includes various forms of physical exercises adapted to the capabilities and needs of older people. These can be moderate aerobic exercises, flexibility and balance exercises, and group activities that promote socialization. Thus, the development of HRPA is an essential tool for supporting elderly IDPs, as it positively affects physical health and promotes social interaction, psychological comfort, and overall well-being. This helps mitigate the consequences of forced displacement and ensures dignified conditions for active and healthy ageing.